PENGARUH DIGITALISASI TERHADAP KINERJA LEMBAGA KEUANGAN DI ERA EKONOMI MODERN - Achmarul Fajar; Enjang Tri Fauwas; Zufawra Ramadhani; Dinda Dwi Syachputri Priandini (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the impact of digitalization on the performance of financial institutions in the modern economic era. The research employs a qualitative approach using a literature review method, drawing from scientific journals, books, and industry reports related to financial digitalization. The findings indicate that digitalization has a positive impact on the performance of financial institutions, particularly in improving operational efficiency, reducing transaction costs, and expanding access to financial services. Furthermore, digitalization promotes product innovation and enhances service quality, leading to increased customer satisfaction and competitiveness. However, the implementation of digitalization also faces several challenges, such as data security risks, digital literacy gaps, and suboptimal regulations. Therefore, comprehensive strategies from financial institutions and supportive government regulations are necessary to ensure effective and sustainable digital transformation.